2017
DOI: 10.1039/c6ra26239b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical study on the corrosion behavior of Ti3SiC2 in 3.5% NaCl solution

Abstract: The differences between the Ti–C and Ti–Si chemical bonds limit the passivation ability, resulting in a decreased passivation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Thus, it can be maintained that metastable oxide and hydroxide of Ti and Si are formed as part of the corrosion product. [38] A similar phenomenon was also reported by Travaglini et al, [41] who investigated the corrosion behavior of Ti 3 SiC 2 in several common acids.…”
Section: Crystallographic-shaped Pitssupporting
confidence: 74%
See 2 more Smart Citations
“…Thus, it can be maintained that metastable oxide and hydroxide of Ti and Si are formed as part of the corrosion product. [38] A similar phenomenon was also reported by Travaglini et al, [41] who investigated the corrosion behavior of Ti 3 SiC 2 in several common acids.…”
Section: Crystallographic-shaped Pitssupporting
confidence: 74%
“…It has high corrosion potential. [ 38 ] Thus, the probability for pit initiation is less than those in other areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the decomposition of the epoxy sealant (probably forming vinyl radicals) in harsh acidic condition led to the carbon contamination. The negative shift of the Ti 2p due to relative increase of Ti 3+ peaks in the sample after the long‐term experiment is likely attributed to the hydroxide formation by the presence of H 2 O as described elsewhere ,. In the case of Pt 4 f, decrease of the Pt 2+ peak led to the slight negative shift and this might be due to reduction of the Pt‐DNS salt during a continuous reduction process (i. e., Pt metal formation).…”
Section: Figurementioning
confidence: 99%
“…The chemical stability of ZnO applied on steel reinforced in concrete investigated using 3.5% NaCl and found that ZnO noticeably improve the corrosion resistance [8]Similar type of electrochemical experiment carried out on pure Titanium and Ti 3 SiC 2 in 3.5% NaCl aqueous solution and found Ti 3 SiC 2 as excellent corrosion inihibitor [9]. An interesting investigation of Ni-P-SiC coatings reveals that the nanoparticles distribution may influence the corrosion phenomenon [10]. A metallic cylinder liners which is one of the a critical component of internal combustion engine have to work under elevated temperature and frequently experience abrasive wear, corrosion/oxidation this leads to economic burden to the manufacturing industries.…”
Section: Introductionmentioning
confidence: 99%